Mental Health Literacy as a Mediator Between Psychological Distress and Self-Stigma in Seeking Psychological Help - Cemile Hurrem AYHAN; Habip GÜNDOĞDU; Mehmet Cihad AKTAS; Kadriye ASLAN; Seda Karakaya ÇATALDAŞ (Archives of Health Science and Research, 2026)
Objective: Mental health literacy (MHL) plays an important role in recognizing psychological problems, reducing stigma, and facilitating professional help-seeking. This study examined the relationships among MHL, psychological distress, and self-stigma in seeking psychological help in a community sample. Methods: This cross-sectional study was conducted between February and May 2024 in Türkiye. Data were collected using a convenience sampling strategy via online platforms and social media networks. A total of 385 adults (M = 28.19, SD = 7.44) completed an online survey including the Mental Health Literacy Scale, the Depression Anxiety Stress Scales, and the Self-Stigma of Seeking Psychological Help Scale. Data were analyzed using descriptive statistics, Pearson correlations, and mediation analysis with the Process Procedure for SPSS (PROCESS, version 3.5.3) macro in SPSS and additional sensitivity analyses examining depression, anxiety, and stress separately. Results: Higher MHL was associated with lower levels of psychological distress and self-stigma. A significant indirect association between psychological distress and self-stigma through MHL was observed in the primary model. However, this pattern was not replicated when depression, anxiety, and stress were examined separately. Across all analyses, MHL was consistently associated with lower self-stigma. Conclusion: The results highlight the importance of strengthening MHL through community-based interventions and public mental health initiatives to reduce stigma and promote timely help-seeking. Future research should examine these mechanisms using longitudinal designs and more diverse populations to inform scalable stigma-reduction strategies. Cite this article as: Ayhan CH, Gündoğdu H, Aktas MC, Aslan K, Çataldaş SK. Mental health literacy as a mediator between psychological distress and self-stigma in seeking psychological help. Arch Health Sci Res. 2026, 13, 0038, doi: 10.5152/ArcHealthSciRes.2026.26038.